Frankenstein doesn't plant petunias - Dadey, Debbie; Jones, Martha (Marcia Thornton); Gurney, John Steven, 1962- (New York : Scholastic, 1993)
The Bailey School kids notice that Frank is very tall and has a lot of scars, and despite the fact that he plants petunias, they wonder if he could be Dr. Victor's man-made monster.
"A Little apple paperback."
570
Keywords: Bailey School kids (Fictitious characters) -- Fiction; Monsters -- Fiction; Schools -- Fiction